Impact of Work Environment and Job Training on Employee Performance - Dini Amalia Putri; Novita Wahyu Setyawati (Draf Solusi Indonesia, 2023)
PT. AELXINDO (Aluminum Extrusion Indonesia) is a manufacturing company engaged in the metal sector, namely aluminum. Yang has a vision, namely to become the largest and best aluminum extrusion company in Indonesia. With that the company is required to measure and improve the performance of employees and the organization that is in it and the company must provide welfare to all employees. The purpose of this study was to determine whether there is an influence between the variables of the Work Environment and Job Training on Employee Performance at PT. ALEXINDO. The data used in this study are primary data obtained in distributing questionnaires to employees. The test results prove that the variables Job Training (X1), Job Training (X2) and Employee Performance (Y) have a significant simultaneous effect with multiple linear results in the F test. These results are obtained from F-count greater than F-table (428,008 > 3.11) while the effect is partially significant through the t test. These results were obtained from the t-count value of the Work Environment variable (X1) of 10.206 and the T-count value of Job Training (X2) of 6.459 which is greater than the T-table value of 1.9896. Then the independent variables namely Work Environment (X1) and Job Training (X2) have an effect on the dependent variable, namely Employee Performance.